Calidad de la gestión organizacional en el desarrollo comunitario de la ciudadela Santa Martha del cantón Pasaje - Nagua Andrade, Jazmín Sabrina; Orellana Barahona, Yarlenny Danisha (Machala: Universidad Técnica de Machala, 2021)
Organizational management is one of the main characteristics for efficient community progress, taking charge of promoting the processes effectively and in the same way that the distribution of the assigned resources is adequate, with the help of good leadership from the directive on duty. The research focuses on the quality of organizational management, of which it has become evident that there are shortcomings for full community development, due to the weak organization, leadership and participation of its directors and residents in activities that aim to obtain community well-being. of its various instabilities. The main objective is based on determining how the quality of organizational management is expressed in community development; Regarding its specific objectives, they consisted of, describing the citizen's perception of the quality of the existing organizational management in the neighborhood, identifying which areas of current community development have made it possible to improve the living conditions of the inhabitants in the citadel and establishing what aspects of organizational management should be strengthened to improve community development, information from which was obtained with the application of the instruments survey, interview and observation sheet. The project was governed by the inductive empirical epistemological approach, with its quantitative methodology, allowing data collection and hypothesis testing, through instruments such as: a survey directed at the inhabitants of the Santa Martha citadel, an interview with the members of directive and direct observation. As a result of the investigation, the scarce organization between residents and the board was obtained, participation is not an action that its inhabitants feel as a responsibility to carry out activities, on the contrary, they consider it as a waste of time in front of their daily activities except for one minimum part that has all the basic services and is not interested in being present, the leadership that from previous directives has not been adequately grasped, the lack of knowledge of the roles and functions of each member of the directive that lead the neighborhood to a decline in future planning and procedures that lead to community development. From the results obtained, the proposal was made as a source of necessary help to reduce the low levels of organization, participation and leadership, which generate stagnation and weakening the progress of the citadel; therefore, the intervention of an organizational strengthening plan was taken as a measure to help the existing problem. If its inhabitants and management reconsider teamwork, the proposal will be executed with satisfaction and in the future obtain the progress that the sector needs by improving the quality of life of the residents. The proposal seeks the union and awareness among inhabitants, including the members of the board of directors and thus promote planning activities for social and economic well-being. Therefore, its specific objectives are: to strengthen the neighborhood council, in management, organization and leadership, and to improve teamwork, for the active participation of community members, in development activities for the sector.
La gestión organizacional es una de las características principales para un eficiente progreso comunitario, encargándose de promover los procesos con efectividad y de la misma forma que la repartición de los recursos asignados sean adecuados, con la ayuda de un buen liderazgo de la directiva de turno. La investigación se concentra en la calidad de gestión organizacional, se ha hecho evidente que existen carencias para un pleno desarrollo comunitario, debido a la débil organización, liderazgo y participación de su directiva y moradores en actividades que tienen como finalidad obtener, bienestar comunal de sus diversas inestabilidades. El objetivo principal se basa en determinar cómo se expresa la calidad de la gestión organizacional en el desarrollo comunitario; en cuanto a sus objetivos específicos, consistieron en: describir, la percepción ciudadana respecto de la calidad de la gestión organizacional existente en el barrio, identificar qué áreas del desarrollo comunitario actual han permitido mejorar las condiciones de vida de los habitantes en la ciudadela y establecer que aspectos de la gestión organizacional deben fortalecerse para mejorar el desarrollo comunitario, información que se obtuvo con la aplicación de los instrumentos (encuesta, entrevista y ficha de observación). El proyecto se rigió desde un enfoque epistemológico empírico inductivo, con su metodología cuantitativa, permitiendo realizar una recopilación de datos y la comprobación de hipótesis, mediante los instrumentos como: una encuesta dirigida a los habitantes de la ciudadela Santa Martha, una entrevista a los miembros de la directiva y una observación directa. Como resultado de la investigación, se obtuvo la escasa organización entre moradores y la directiva, la participación no es una acción que sus habitantes sientan como responsabilidad para efectuar actividades, al contrario la consideran como una pérdida de tiempo ante sus actividades diarias a excepción de una mínima parte que cuenta con todos los servicios básicos y no se interesan en hacerse presentes, el liderazgo que desde directivas anteriores no asido adecuado, la falta de conocimiento de roles y funciones de cada integrante de la directiva que llevan al barrio a un retroceso de futuras planificaciones y gestiones que conlleven al desarrollo comunitario. De los resultados obtenidos, se procedió a realizar la propuesta como fuente de ayuda necesaria para reducir los bajos niveles de organización, participación y liderazgo, que generan un estancamiento y debilitamiento al progreso de la ciudadela; por lo tanto la intervención de un plan de fortalecimiento organizacional se tomó como medida de ayuda a la problemática existente. Si sus habitantes y directiva reconsideran el trabajo en equipo, la propuesta será ejecutada con satisfacción y a futuro obtener el progreso que necesita el sector mejorando la calidad de vida de los moradores. La propuesta anhela la unión y concientización entre habitantes, incluyendo a los miembros de la directiva y así se promuevan actividades de planificación para el bienestar social y económico. Por lo tanto sus Objetivos específicos son, fortalecer al consejo barrial, en gestión, organización y liderazgo, y mejorar el trabajo en equipo, para la participación activa de los miembros de la comunidad, en actividades de desarrollo para el sector.
Keywords: ORGANIZACION; LIDERAZGO; GESTION ORGANIZACIONAL; DESARROLLO COMUNITARIO